RE-DESAIN KEMASAN HERBAL TEA PT. ANDALAS SITAWA FITOLAB - RITA YUNIARTI, Dra. Zubaidah, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Based on the findings of the problem through an interview with the owner of Herbal Tea PT. AndalasSitawaFitolab, Mr. Prof. Deddi Prima Putra on December 20 and 27, 2017.There’s no optimal packaging yet for these herbal tea products available in the company, so it is necessary to re-design it as one of the promotional media that is able to provide information and create the image impression to influence competitors. The purpose of packaging re-design is to maximize the packaging design to achieve the competitiveness of the competitor and the selling power of a product in marketing by (1) Creating a new packaging design with a simple but still attractive look. (2) Creating a new and informative packaging design so as to attract potential customers to buy. (3) Improving existing weaknesses in the packaging to be able to increase the selling value of the product to increase the company's turnover. The design methodology used in the re-design of herbal tea packaging is through descriptive qualitative analysis method with SWOT analysis approach (Strength, Weakness, Opportunity, and Treatment) that can answer and solve existing problems and be able to develop creative design ideas. The design results of the re-design of herbal tea packaging as the main media are in the form of box packaging with size (13x7x8) cm, Hang Tag, and Secondary Packaging in the form of teabag packaging. Then supported by other supporting media such as Posters, X-banners, Stickers, Mugs, T-shirts, Calendar, Paper Bag.Keywords: Re-design, Packaging, PT. Andalas SitawaFitolab